2011
DOI: 10.2217/imt.11.97
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient Survival in a Phase I Trial of Systemic Targeted α-Therapy for Metastatic Melanoma

Abstract: Targeted α-therapy is an experimental approach to the management of cancer. Short range α-particle radiation from a radioisotope attached to a targeting monoclonal antibody kills targeted cancer cells. Survival results are analyzed from a previously reported Phase I study of systemic targeted α-therapy for patients with stage IV metastatic melanoma or in-transit metastases. Following intravenous administration of 46-925 MBq of the α-immunoconjugate, (213)Bi-cDTPA-9.2.27, 38 patients were followed to observe re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 20 publications
1
57
1
Order By: Relevance
“…To date, clinical alpha particle RIT has been investigated in patients with hematological malignancies [54], [55], ovarian [56], melanoma [57] or brain tumors [58]. Our study gives preclinical rationale for the ongoing Phase I study (NCT01384253) as the toxicity was less than previously reported suggesting the potential for dose escalation with acceptable toxicity and a higher therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 80%
“…To date, clinical alpha particle RIT has been investigated in patients with hematological malignancies [54], [55], ovarian [56], melanoma [57] or brain tumors [58]. Our study gives preclinical rationale for the ongoing Phase I study (NCT01384253) as the toxicity was less than previously reported suggesting the potential for dose escalation with acceptable toxicity and a higher therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 80%
“…Targeted alpha particle emitters are currently under clinical investigations for leukemia (32) ovarian cancer (33), malignant melanoma (34) and glioblastoma (35) because of their high potency. The recent clinical success of Radium-223 (Alpharadin) in castration-resistant prostate cancer with bone metastases (36) supports further development of alpha particle emitters and highlights the importance of a unique biological mechanism in the highly specific accumulation of targeted radioisotopes.…”
Section: Discussionmentioning
confidence: 99%
“…The range of α-particles is rather short in tissue in comparison to beta particles (50–80 µm vs. 0.8–12 mm); they have a much higher linear energy transfer (100 keV/µm vs. 0.2 keV/µm) [129]. Currently, there are clinical trials for different types of cancer with targeted high potent α-emitters [132,133,134]. In an in vitro study 213 Bi-labeled CHX-A′′DTPA-cetuximab showed effective double-strand breaks on different human breast cancer cells, but for an approach in patients the safety of targeted α-emitter-labeled radioconjugates has to be evaluated [135].…”
Section: Radiolabeled Cetuximabmentioning
confidence: 99%